Design and development of transmission for two-seated urban car - Maaruf, Muhamad (2010)
This thesis is aim on designing and customizes the transmission from 4 stroke Modenas Kriss 110cc engine to be used in two seated urban car. Design requirement followed by the rules of the Eco-challenge marathon race. The suitable gear is to be identified and selected because of the transmission is decided to use only single gear ratio that suitable and the power produce must be approximate nearly to the power required to avoid losses. It‟s important because the design of two seated urban car required the participant to design and development two seated urban car that have low fuel consumption. The design will carry out to produce power that approximate enough to the required power and also have a suitable design for two seated urban car that will be design. In this thesis the result to use a single gear ratio is chosen. This is because of the result from the analysis by calculation showed that power produce is near to the power required to move the car. Then finally this condition can make the car running as efficient as possible.